Czech Equivalents of English -ing Forms in Fiction - Bisová, Jitka (Univerzita Pardubice, 2010)
The bachelor paper focuses on the occurrence of the English gerund and the participle in relation to their syntactic functions in the fictional literature. The attention is also paid to the Czech equivalents of these -ing forms. The selected English text from fiction is analysed in the paper and compared with its Czech translation. The valency, the gradience, the language typology, the Czech translation of the English -ing forms and the fictional style are described because they relate to the subject of the bachelor paper.
České ekvivalenty anglických -ingových tvarů v umělecké literatuře
Keywords: valence; gerundium; participium; syntaktická funkce; fikce; -ing formy; ekvivalenty; valency; gerund; participle; syntactic function; gradience; fiction; -ing forms; equivalents